Simple water purification - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Where water is scarce, irrigation is a luxury. One way to extend precious resources is to use waste water but, for hygiene reasons, only after purification. Classical purification plants are expensive and require skilled personnel. A new technique,...